Conducting case study research for business and management students - Lee, Bill; Saunders, M. N. K. (London : SAGE Publications Ltd, 2017)
Part of SAGE's Mastering Business Research Methods series, conceived and edited by Bill Lee, Mark N. K. Saunders and Vadake K. Narayanan, the series is designed to support business and management students with their research-based dissertations by providing in-depth and practical guidance on using a chosen method of data collection or analysis. The books are written in a concise and accessible way, and contain a range of features, including checklists and a glossary, designed to support self-guided research. In Case Study Research, Bill Lee and Mark N.K. Saunders describe the properties of case study designs in organizational research, exploring the uses, advantages and limitations of case research. They also demonstrate the flexibility that case designs offer, and challenges the myths surrounding this approach. Ideal for Business and Management students reading for a Master's degree, each book in the series may also serve as reference books for doctoral students and faculty members interested in the method.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Business -- Research -- Methodology